Pemanfaatan Aplikasi Labirin dalam Melatih Keterampilan Problem Solving Siswa SD - Umi Mayalatul Akhadiyah; Shiva Tya Alviani; Kamelia Wahyu Ningsih; Nofan Zulfahmi (Jurnal Bintang Pendidikan Indonesia, 2024)
This research aims to analyze the use of the maze application in training elementary school (SD) students' problem solving skills. Problem solving is an important skill in facing the challenges of the modern era, which includes the ability to think creatively, analytically and logistically. Through a literature study-based literature study method, this research found that the labyrinth application not only increases students' ability to think critically, but also trains concentration, perseverance, and hand-eye coordination. In addition, the interactive and fun application format can increase student learning motivation, increasing the learning experience effectively and entertainingly. This study also highlights the importance of integrating technology in learning and the role of teachers in optimizing the implementation of this application according to the curriculum. With good planning, maze applications can be an innovative educational tool to support students' cognitive and motor development, while preparing them to face future challenges.